Finite-time sideslip observer-based synchronized path-following control of multiple unmanned underwater vehicles. (1st December 2020) - Qu, Xingru; Liang, Xiao; Hou, Yuanhang; Li, Ye; Zhang, Rubo
Abstract: A synchronized path-following control scheme for a cluster of networked unmanned underwater vehicles (UUVs) suffering from unknown dynamics and unknown sideslip angles is proposed in this paper. On the basis of UUV kinematics model, the unknown sideslip angles are successfully identified using finite-time observers, thereby ensuring high accurate path-following performance. By virtue of individual path-following and consensus information, the coordinated light-of-sight guidance and the path update protocol are employed, respectively, which provide sufficient technology support for desired formation pattern. Simultaneously, an adaptive approximation is incorporated into the distributed dynamics controllers, where the lumped unknowns involving modeling uncertainties and time-varying ocean currents are estimated accurately, thereby enhancing the formation system anti-disturbance performance. It is proven that, with the proposed scheme, all vehicles can track the multiple parametric paths synchronously and the entire closed-loop system is globally asymptotically stable. Finally, simulation results for coordinated path-following of four underactuated UUVs are exhibited and discussed. Highlights: Coordinated path-following control for UUVs is researched. Multiple geometry paths are tracked simultaneously. A novel finite-time sideslip observer is created. Path-following and formation keeping are decoupled. Distributed anti-disturbance controllers are employed.